(untitled) - WISETIOKO, PANCA (Language Horizon: Journal of Language Studies, 2014)
Death Instinct In Mary Shelley’s Frankenstein Panca Wisetioko English Literature Faculty of Language and Arts State University of Surabaya y.panca.wise@gmail.com Drs. Much. Khoiri, M.Si. English Department Faculty of Language and Arts State University of Surabaya much_choiri@yahoo.com Abstrak Naluri dapat digambarkan sebagai kekuatan manusia dan dianggap ada di balik ketegangan yang disebabkan oleh kebutuhan dari id. Id dapat berkembang menjadi kekuatan destruktif yang disebut sebagai insting kematian dan ekspresi insting kematian disebut sebagai agresi. Dalam Mary Shelley Frankenstein, dua karakter utama menggambarkan insting kematian yang mempengaruhi pikiran dan tindakan yang bertujuan untuk menghancurkan atau membunuh siapa pun. Studi ini berfokus pada dua masalah , ( 1 ) bagaimana insting kematian digambarkan dalam Mary Shelley Frankenstein? dan ( 2 ) Mengapa si monster dan Dr Frankenstein menggambarkan agresi sebagai komponen dari insting kematian dalam hidup mereka di Mary Shelley Frankenstein? Data tesis diambil dari novel sebagai sumber utama dan membaca secara intensif adalah langkah berikutnya dalam analisis. Konsep yang akan digunakan meliputi konsep naluri dan insting kematian oleh Freud dan Susan , dan juga istilah agresi oleh Subaidah. Untuk menjawab masalah pertama, penelitian ini menggunakan istilah Freud tentang insting kematian dan didukung oleh konsep dari Susan tentang insting. Masalah kedua dijawab dengan menggunakan konsep dari Subaidah tentang agresi. Yang terakhir, analisis mengungkapkan bahwa insting kematian digambarkan oleh monster melalui tindakannya ketika membunuh putra Dr Frankenstein, teman, dan anggota keluarga yang lain. Selain itu, Dr Frankenstein juga menggambarkan insting kematian melalui intensi untuk menghancurkan si monster. Keduanya mendapatkan kesenangan dan kepuasan dari tindakan mereka. Dr Frankenstein dan monster tersebut menggambarkan insting kematian karena rasa marah dan frustrasi antara satu sama lain. Kata kunci : insting kematian, sadar, id, agresi. Abstract Instincts can be described as the forces of human and assume to exist behind the tensions which are caused by the needs of the id. The id can develop into destructive force which is called as death instinct and the expression of death instinct called as the aggression. In Mary Shelley’s Frankenstein, the two main characters depict the death instinct that influence their minds and actions which purpose to destroy or kill anyone. The study focuses on two problems, (1) how is death instinct depicted in Mary Shelley’s Frankenstein? and (2) Why do the monster and Dr. Frankenstein represent the aggression as the component of death instinct in their life in Mary Shelley’s Frankenstein? The data of thesis are taken from the novel as the main source and intensive reading is the next step of analysis. The concept that will be used includes the concepts of instinct and death instinct by Freud and Susan, and the terms of aggression by Subaidah. To answer the first problem, this study uses Freud’s terms about death instinct and supported by Susan’s terms about the concepts of instinct. The second problem is answered by using Subaidah’s terms about the aggression. Last of all, the analysis reveals that death instinct depicted by the monster through his action in killing Dr. Frankenstein’s son, friends, and his other family members. Besides, Dr. Frankenstein also represents death instinct through his intension to destroy the monster. Both of them get pleasure and satisfaction from their actions. Dr. Frankenstein and the monster represent death instinct because the feeling of anger and frustration each other. Keywords: death instinct, unconscious, id, aggression. INTRODUCTION Horror literature is focusing on death, the afterlife, evil, the demonic and the principle of the thing embodied in the person. In stories, there are many gothic creatures, like witches, vam-pires, demonic, werewolves, and ghost. This genre has ancient origins which were reformulated in the 18th century as Gothic horror, with publication of the Castle of Otranto (1764) by Horace Walpole. After that century, the Gothic tradition blossomed into the genre modern readers call horror literature in the 19th century. In this era, some great works and characters of horror have been adapted by some films and cinema. It shows to the world that some horror writers have given contributions. Some literary works concern with horror in genre are Mary Shelley’s Frankenstein (1818), Edgar Allan Poe’s short stories, the works of Sheridan Le Fanu, Robert Louis Stevenson’s Strange Case of Dr. Jekyll and Mr. Hyde (1886), Oscar Wilde’s The Picture of Dorian Gray (1890), and Bram Stoker’s Dracula (1897). One of the most famous horror novels is Frankenstein which was written by Mary Shelley in 19th century. In that era, the novel was also being a very important work in literature contributions that had made by women acceptable. Although Mary Shelley wrote many novels, none of her another works was popular like Frankenstein, which still gains its popularity until today. (www.famousauthors.org/mary-shelley) A study of the scientific aspects of the novel is so popular and timely that the present author and others have presented or published papers on this theme (Ginn, 2003; Ketterer, 1997). The National Library of Medicine has developed a traveling exhibit examining Frankenstein’s science, and a conference dedicated to this theme (Frankenstein’s Science: Theories of Human Nature in the 18th and 19th Centuries) was held in Canberra, in 2003. (nlm.nih.gov/hmd/frankenstein/frankhome.html) The author of Frankenstein, Mary Shelley, is often known as Mary Wollstonecraft Shelley. She was one of the famous horror writers in the world. Mary was a British woman novelist, short story writer, dramatist, essayist, biographer, travel writer, and editor of the works of her husband, Percy Bysshe Shelley who was a Romantic poet and a philosopher. And she was the daughter of the political philosopher William Godwin and Mary Wollstonecraft who was famous as the writer, philosopher, and feminist. She wrote many horror novels including Lodore (1835), Faulkner (1937), Mathilde (1959), Valperga or the Life and Adventures of Castruccia, Prince of Lucca (1823), The Last Man (1826), and The Fortunes of Perkin Warbeck (1830). She also wrote a number of short stories, travelogues and other works, but Frankenstein has been the unforgettable works of her. Mary Shelley herself is best remembered by literature world as the author of Frankenstein. The story of this novel tells about an ambitious inventor named Dr. Frankenstein who forces to create a human from various body parts taken from some corpses in graves. He believes that he can create a perfect human which is stronger and smarter than any ordinary human being. He finally finishes his project in making that creature. But, the result does not alike what he expects before. The creature looks like a monster rather than a human. It makes Dr. Frankenstein rejecting and dumping him. The monster cannot accept how the doctor treats him because the doctor himself is as the creator and the father of the monster who should love him and treat him well like God who creates and loves human beings. The doctor always mocks the monster about his physical appearance condition which is very ugly, even looks like a devil. The monster is very angry with the doctor. He hates the doctor a lot and he wants to kill the doctor as a revenge. Not only the doctor, but the monster also hates human being because people treats him as bad as the doctor even though the monster has given aid to humans. The other thing that makes him hate human is because there is no one wants to be his friends. Everyone who meets him always run, hit and shout that he is a monster. He feels depressed and desperate about his life and his condition. He always asks to himself why he cannot be an acceptable person in his real life. After he got many bad things, he says that he will kill all human being, especially a man who created him and all persons that he loves. One by one, everyone who loved by Dr. Frankenstein were killed by the monster. The doctor himself also promises to kill his creature because of those accidents. Both of them have death instinct to kill each other. In the end of the story, Dr. Frankenstein dies in the way when he looks for the monster. The monster feels very satisfied with his death, after that he falls down to the sea, and no one never see him again. Death instinct which is depicted in Frankenstein and it based on the concepts of Sigmund Freud. According to Orbach (2007), his conceptualization of the death instinct behaviors reflecting self-destructive tendencies, guilt feelings, suicide, melancholia, masochism and sadism are furnished with a motivational force of their own, as well as a specific mechanism of action, that is the repetition compulsion. The death instinct drives man to the ultimate state of quiescence – death through the urge inherent in organic life to restore an earlier state of things. This novel presents death instinct that is depicted by Dr. Frankenstein and the monster as the characters of Shelley’s Frankenstein. There is a stage which is being the part of the story that represents the instinct. It is shown when the monster killed Frankenstein’s son (Shelley, 1994: 179). The action that has been done by the monster is the representation of the death instinct, especially the purpose of death instinct. It depends on Freud terms (1949: 6), he explained that the purpose of death instinct is to kill someone or destroy something. The another things that are shown in this novel is the reason of the characters when they want to do aggression which is being the component of death instinct (Subaidah, 2012), she also said that anger feeling becomes the one of the reasons or factors to do aggression to another person. The reason is depicted in the part of the story when the monster becomes angry and wants to kill all human and the doctor who is being his creator (Shelley, 1994: 172) Depends on Schultz (2008: 56), Freud also developed three parts of mind. He drew that the parts are the conscious, the preconscious, and the unconscious. Aside from the three levels of consciousness, Freud believed there to be three parts of personality. There are the id, the ego, and the superego. That is why this study is being the study that analysis about death instinct and its reason because there are many statements and actions that has been represented by the characters of the novel, especially about death instinct and its reason. RESEARCH METHOD To reveal the death instinct of the characters, this study applies the concept of human instinct in analyzing the problems. The concept which will be applied to discuss the matter in this study is the psychoanalysis theory especially the concept of death instinct by Sigmund Freud. The main data source of this study is Mary Shelley’s Frankenstein, while the data which is used in this study is in the form of statements which are taken from the novel Frankenstein that reveals the death instinct of the characters, Dr. Frankenstein and the monster. This study will be conducted by using descriptive-qualitative method. It means that this study provides descriptive analysis without using any statistic or number in analyzing the subject matter. The concept applied to discuss the matter in this study is death instinct which is mostly described by Mary Shelley in her novel which titled is Frankenstein. Since the focus of the study becomes clearer, data classification is needed. After collecting and classifying such complete data, the study arranges it in order, so that the study is able to get good understanding about the story of the novel and the issue which is going to be analyzed. In the next step, the story is being analyzed by using theory that is Instinct theory. Here, in analyzing death instinct of human being, this study tries to elaborate dialogue, conflict, and action in the novel and applies the concept. Then, the next step is to reveal how is the death instinct of the characters, which is viewed from the theory of psychoanalysis by Sigmund Freud. Finally, this research provides a deep analysis on the death instinct of Dr. Frankenstein and the monster in Mary Shelley’s Frankenstein. DEFINITION OF INSTINCT The forces which human assume to exist behind the tensions caused by the needs of the id are called instincts. It can change their aim (by displacement) and also that they can replace one another-the energy of one instinct passing over another. This also consists in the satisfaction of its innate needs. (Freud, 1949: 5) Instinct also can be described as the basic elements of the personality, the motivating forces that drive behavior and determine its direction. Freud’s German term for this concept is Trieb, which is best translated as a driving force or impulse (Bettelheim, 1984). Instincts are a form of energy—transformed physiological energy—that connects the body’s needs with the mind’s wishes. The stimuli (hunger or thirst, for example) for instincts are internal. When a need such as hunger is aroused in the body, it generates a condition of physiological excitation or energy. The mind transforms this bodily energy into a wish. It is this wish—the mental representation of the physiological need—that is the instinct or driving force that motivates the person to behave in a way that satisfies the need. A hungry person, for example, will act to satisfy his or her need by looking for food. The instinct is not the bodily state; rather, it is the bodily need transformed into a mental state, a wish. When the body is in a state of need, the person experiences a feeling of tension or pressure. The aim of an instinct is to satisfy the need and thereby reduce the tension. Freud’s theory can be called a homeostatic approach insofar as it suggests that people are motivated to restore and maintain a condition of physiological equilibrium, or balance, to keep the body free of tension. Freud believed that people always experience a certain amount of instinctual tension and that people must continually act to reduce it. It is not possible to escape the pressure of our physiological needs as we might escape some annoying stimulus in our external environment. This means that instincts are always influencing our behavior, in a cycle of need leading to reduction of need. People may take different paths to satisfy their needs. For example, the sex Drives may be satisfied by heterosexual behavior, homosexual behavior, or auto sexual behavior, or the sex drive may be channeled into some other form of activity. Freud thought that psychic energy could be displaced to substitute objects, and this displacement was of primary importance in determining an individual’s personality. Although the instincts are the exclusive source of energy for human behavior, the resulting energy can be invested in a variety of activities. This helps explain the diversity people see in human behavior. All the interests, preferences, and attitudes people display as adults were believed by Freud to be displacements of energy from the original objects that satisfied the instinctual needs. Freud grouped the instincts into two categories: life instincts and death instincts. The life instincts serve the purpose of survival of the individual and the species by seeking to satisfy the needs for food, water, air, and sex. The life instincts are oriented toward growth and development. The psychic energy manifested by the life instincts is the libido. The libido can be attached to or invested in objects, a concept Freud called cathexis. If you like your roommate, for example, Freud would say that your libido is cathected to him or her. The life instinct Freud considered most important for the personality is sex, which he defined in broad terms. He did not refer solely to the erotic but included almost all pleasurable behaviors and thoughts. Freud regarded sex as our primary motivation. Erotic wishes arise from the body’s erogenous zones: the mouth, anus, and sex organs. He suggested that people are predominantly pleasure-seeking beings, and much of his personality theory revolves around the necessity of inhibiting or suppressing our sexual longings. In opposition to the life instincts, Freud postulated the destructive or death instincts. Drawing from biology, he stated the obvious fact that all living things decay and die, returning to their original inanimate state, and he proposed that people have an unconscious wish to die. One component of the death instincts is the aggressive drive, described as the wish to die turned against objects other than the self. The aggressive drive compels us to destroy, conquer, and kill. Freud came to consider aggression as compelling a part of human nature as sex. Freud developed the notion of the death instincts late in life, as a reflection of his own experiences. He endured the physiological and psychological debilitations of age, his cancer worsened, and he witnessed the carnage of World War I. One of his daughters died at the age of 26, leaving two young children. All these events affected him deeply, and, as a result, death and aggression became major themes in his theory. In his later years, Freud dreaded his own death, and exhibited hostility, hatred, and aggressiveness toward colleagues and disciples who disputed his views and left his psychoanalytic circle. THE CHARACTERISTICS OF INSTINCT According to Susan (2004: 42), there are some characteristics of instincts. She summarized the four aspects of instincts: source, pressure, aim, dan object. The first is source. All physic energy is derived from biological processes in some parts or organs of the body. There is no separate, exclusively mental energy. The amount of energy a person has does not change throughout a lifetime although it is transformed so that it is invested differently. At first, psychic energy is directed toward biological needs. As development occurs, this same energy can be redirected into other investment, such as interpersonal relationships and work. The second is pressure. It refers to its force or motivational quality. It corresponds to the strength of the instinctual drive; it is high when the drive is not satisfied and falls when the needs is met. For example, a hungry infant has a high pressure of the hunger drive: one just fed has hunger at a low pressure. When the pressure is low, the instinct may nt have noticeable effect; but when the pressure is high, it may break through, interrupting other activities. A hungry baby wakes up, for example, and it depends on Susan (2004: 42). The next characteristic is aim, the function of instinct according to a principle of homeostatis, or steady state, a principle borrowed from biology. Instinct aim to preserve the ideal steady state for organism (Susan, 2004: 42). Changes moving away from this steady state are experienced as tension. The aim of all instincts is to reduce tension, which is pleasurable. Instincts operate according to what Freud called the pleasure principle, they aim simply to produce pleasure by reducing tension, immediately and without regard to reality constraints. Tension reduction occurs when the original biological instinct is directly satisfied, for example, when a hungry infant is fed or when sexually aroused adult achieves orgasm. It would be a mistake, however, to conclude that only direct biological drive satisfaction can reduce tension. Some transformations of libido also allow tension reduction (Susan, 2004: 42). Such healthy, socially acceptable ways of reducing tension are termed sublimation. However, indirect expressions of libido do not always reduce the pressure of instinct. Thus a chronic deviation from a restful, homeostatic state occurs in individuals who have not found ways to reduce tension, such as neurotics (Susan, 2004: 42). The last is object, this characteristic of instinct is about the person or thing in the world that is desired so that the instinct can be satisfied, it based on Susan’s terms about instinct (2004: 42). For example, the object of the hunger drive of an infant is the mother’s breast: it brings satisfaction. The object of a sexually aroused adult is a sexual partner. Investment of psychic energy in a particular object is called cathexis. It is with respect to the object of an instinct that there is the most variation, the most influence of experience on a person’s fundamental motivations. Some sexually aroused men look for a woman just like mother; others look for a very different kind of woman or for a man, or even for underwear or a child or any of a vast assortment of sexual objects. Women are also very widely in their choice of sexual objects. The fact that libido is capable of being directed toward so many diverse objects; not fixed biologically, is termed the plaslicily of instinct. This is much greater in humans than in lower animals, who seem to come with instinct “prewired” to very specific objects. Learning from experience-selecting objects from the possibilities in the environment and learning to adapt to reality-occurs in the ego. The ego, in contrast, the functions according to a very primitive mechanism, called primary process. DEATH INSTINCT (THANATOS) Freud believed that every human had a life and death instinct. The life instinct is called eros while death instinct is called thanatos. Death instinct is a destructive force directing us inevitably toward death, the ultimate release from the tension of living. It motivates all kind of aggression including war and suicide. (Susan, 2004: 41) According to Orbach (2007: 266), Freud’s conceptualization of the death instinct behavior reflecting self-destructive tendencies, guilt feelings, suicide, melancholia, mascochism and sadism are furnished with a motivational force of their own, as well as with a specific mechanism of action, that is the repetition compulsion. Death instinct drives man to the ultimate state of quiescence – death through the urge inherent organic life to restore an earlier state of things. The purpose of death instinct is to destroy things and to reduce living things to an inorganic state. (Freud, 1949: 5) Freud also explains that death instinct is intended to individuals typically two ways, to himself or others to outside themselves. Death instinct is redirected looking at people in an action of suicide, while the instinct redirected to death outside or anyone else to do something when they want to kill, persecute, or destroy others. Death instinct also encourages people to ruin people, and the aggressive drive pushes the distribution of people who are not killed. To maintain them, death instinct will against life with generally energy which steer out, ??intended to others. Freud assumes that every human in their subconscious part, will have a passion for dead, a desire is always mightily repressed by ego. The component of the death instincts is aggression. (http://12013pus.blogspot.com/2013/06/sigmund-freud.html) The most influenced component of the death instincts is the aggressive drive. It is described as a wish to against objects rather than a self. The aggressive drive compels us to destroy, conquer and kill. Freud comes to consider aggression as compelling a part of human nature. Freud also recognizes that the object of the aggressive instinct is fighting, and it is always for the gratification of the id. Most aggressive behavioral traits are destructive. They are considered to be the consequence of dysfunctional character formation. However, some of these instinctual traits may be momentary. Freud suggests that the aggressivity is related to death threat. This means that it can apply to the individual as well as to his or her relation with others. According to Subaidah (2012), aggression is a behavior that can hurt others. There are several factors that influence the aggression. Each factors may differed from one’s act of aggression in which it is more dependent on an act of aggression itself and where the act of aggression took place. Lately a lot of aggression is going on in the social sphere such as at school and other social spheres. She explains that there are several factors that cause aggression or aggressiveness: 1. Biological factors There are several biological factors that influence aggressive behavior: a. The gene seems to affect the formation of the neural systems that regulate the aggressive behavior. b. Brain systems which are not involved in aggression were found to reinforce or inhibit the neural circuits that control the aggression. c. Blood chemistry (particularly the sex hormones which is partly determined heredity) can also influence aggressive behavior. 2. The Instinct According to Sigmund Freud, he explains that in humans there are two kinds of instincts which are called as eros (life instinct) and thanatos (death instinct). Aggression is an expression of the death instinct and it may be directed to other people or other targets (external) and can also to themselves (internal). 3. The Anger feeling Anger is the emotion that has the characteristics of the parasympathetic nervous system activity which is high. It is the feeling of strong dislike feeling commonly conducted due to an error, which may be manifestly wrong or maybe not. At the moment, there is a desire to attack which includes by angry, punching, destroy or throw something, it usually arises cruel mind. When things are distributed and there is aggressive behavior. 4. Frustration feeling Frustration occurs when someone blocked by something in achieving a goal, needs, desires, expectations or specific actions. Aggression is the way to respond the frustration feeling. Poor time naughty teen is a result of frustration which is related to the amount of unemployed time, financial mediocre and the requirements that must be fulfilled but difficult to achieve. As a result, they become irritable and aggressive. (jambeekidul.blogspot.com/2012/05/agresi.html) The Death Instinct depicted by Dr. Frankenstein and The Monster in Mary’s Frankenstein In the novel, death instinct depicted is firstly depicted by Dr. Frankenstein when he meets the monster in the field of ice. When he enjoys the atmosphere of the nature around him, suddenly he sees the figure of man and the creature comes nearly to him with super human speed. He really surprised when he sees the creature that stands in front of him. The creature is the monster that was made by him, but the doctor never wants to see the monster because it looks so ugly and scary. So the doctor wants to kill that monster by himself. The next part which depicts the death instinct is shown by the monster. It happens when the doctor sees something like a human but it looks different from the ordinary human. The creature comes nearly to him, and the doctor is surprised because the creature is the person who is seemed like a monster. The doctor said many bad words to him, but there is the time when the monster wants to make a deal with Frankenstein. The monster is being the unacceptable person in the real life, there is no one can accept his condition. The monster wants to ask about something which is related to his condition but he says that if the doctor refuses his request, the monster will kill him. The next quote is shown by Dr. Frankenstein and his creature. After the monster asked something with the doctor and want to make a deal with the doctor, Frankenstein who is being the creator of the monster answered the kind of thing that has been asked by the monster. Death instinct is depicted in the some words. In those words, the doctor want to take the monster’s life or in another meaning, it means that the doctor want to kill the monster. It depends on Freud terms about death instinct, he explains that the purpose of death instinct is to kill someone. The next part which shows death instinct in the novel, there is no deal between Dr. Frankenstein and the monster. The doctor feels very angry and hates the monster because the condition of the monster itself. After that, the doctor does the action that is shown in the quotation as the part of the story. In some parts of the statements, the doctor wants to attack the monster by himself. It shows that Frankenstein want to expressing his feeling that represent the purpose of death instinct. It is like Freud terms, he explains that the purpose of the death instinct of human being is to destroy or kill another creature. The next statement is said by Dr. Frankenstein, it happens when the doctor tries to hit the monster. But the monster can dodge the action of the doctor. The monster still wants to make a deal with the doctor. The monster tells about his sadness feeling to the doctor. But the words that were said by the monster cannot make the doctor’s heart follow what the monster wants. In the time of the novel, the doctor feels angry and says many words to the monster. There are some words which depicts the death instinct of the doctor and describe that Frankenstein want to fight with the monster and kills him. The next statement is said by the monster, he continuous his journey, and after that he arrives at Geneva. Directly, he looks for the hiding place. Then he takes a rest, and suddenly the little boy comes to him. He thinks that this boy does not have a negative thought like the other people. But he is wrong, this boy looks so scared, he tries to talk with the boy. Suddenly, the boy says many bad words to him, and he tells Frankenstein as a name of the person that the monster really hates. Finally, the monster wants to kill this boy, it is depicted in the some words. He describes the death instinct and his actions that he will do in this part of the statement. Based on Freud (1949: 6), the purpose of death instinct is to kill or destroy something. The Reason of the Characters Who Represent the Aggression In this Mary Shelley’s Frankenstein, there are many aggressions that are depicted in the some parts or in the some statement that were said by the characters, and there are many things that are being the reason of the character to do their aggression to another. Dr. Frankenstein and the monster show the causes or the factors of aggression based on their actions and quotations. The factors will be explained in these parts of thesis based on Subaidah’s terms of aggression (2012). Aggression is firstly shown by Dr. Frankenstein when he sees a person in the ice field. When he really enjoys the natural situation around him, suddenly he finds the figure of human and the creature comes nearly to him with super human speed. He really surprised when he sees the creature which stands in front of him. The creature is the monster that was made by him, but the doctor never wants to see the monster because it looks so ugly and scary. In some statement, there is a factor that will be explained. There are some words which show the anger feeling of the doctor as the main factor which influences him and it is the reason of him to do the aggression to the monster. The next statement is continuing the conversation before that happened between Dr. Frankenstein and his creature. After the monster asked something with the doctor and want to make a deal with the doctor, Frankenstein who is being the creator of the monster answered the kind of thing that has been asked by the monster. He said some words to answer what the monster want. Those words describe the anger feeling of the doctor and also show that the doctor really does not like the monster because the psychical condition of the monster. It is to be his reason to do the aggression to the monster. This explanation similar with Subaidah’s terms, she explains that the anger is one of the factors that can influence a person to do aggression to another person, and the thing that can cause the anger is because the feeling of dislike so strong. The next part of the story in the novel, there is no deal between Dr. Frankenstein and the monster. The doctor feels very angry and hates the monster because the condition of the monster itself. After that, the doctor does the action that is shown in the quotation as the part of the story. There are some words which show the reason of the doctor when he wants to destroy the monster. The doctor describes his feeling which influences him to be aggressive clearly in this part of his statement. These feeling can influence someone to be an aggressive person, it means that the person wants to kill or destroy the other person. This is has similarity with Subaidah’s term, she explains that the reason of the person to do aggression is because their angry feeling. The next statement is said by the monster. It is continuing from the statements before. After the doctor asked him to go, the monster is still trying to tell about the experiences that he got in his life. He tells many things to the doctor, he hopes the doctor will agree to make a deal with him. And in the situation that is described in the novel, the monster says something about his feelings to the doctor. He says the words to Dr. Frankenstein. There are some words that show the anger feeling of the monster. The words describe the reason of him when he wants to do the aggression to his enemies and he really wants to destroy them. Based on Subaidah (2012), anger is the factor for the people to do aggression to another, and the dislike feeling because of the mistaken things that has been done by a person will influence a person angry with the another people. There are also some words which show the mistakes of the doctor and the human that cause the anger of the monster. Dr. Frankenstein has done something that make the monster feel dislike and angry with him, this is also done by the other person. The next statement is still based on the story of the monster. After he went to forest, he lived in a place. He felt desperate because of human actions. He remembered the accident that he got from De Lacey family, especially from Felix. He felt so angry, he wanted to destroy everything near him. There are some words which represent the anger feeling of the monster, it is described clearly in the part of the statement. It becomes his main feeling when he thinks to destroy something or injury the human and it also shows the factor that influences him when he cannot control himself and change into an aggressive person. The anger feeling is the dominant feeling that becomes the reason for him to do aggression to human being. This is similar with Subaidah’s terms which describes the aggression can be done by a person because the anger feeling that were caused by the mistake of the another person, it can grow up the dislike feeling of the person. CONCLUSION Based on the analysis in the previous chapter, there are two important conclusions drawn: the death instinct and the aggression which is being the component of death instinct based on the characters. First, it represents death instinct which is shown by Dr. Frankenstein and the monster who is his creature. Death instinct has some steps which include unconscious and id, it also has a purpose to destroy something or kill someone. By those steps and the purposes of death instinct, it can be concluded that the doctor has death instinct when he wants to kill or destroy the monster, and the monster wants to kill the doctor and all people who gave him many bad experiences in his life, such as when he killed Frankenstein’s son. They show death instinct by killing or destroy something based on their main feelings and instinct itself. The unconscious is being the important part of instinct because it drives and controls all human mind and action that they want to do to another people. The next step that becomes the part of unconscious is the id of the characters. They will do something that will give them a pleasure or satisfied feeling, it based on their id. These part will develop to death instinct when they have some wishes to destroy anything or kill anyone. It is shown when the monster killed the doctor’s wife, some his families member, and his friends, it is also depicted when the doctor really wants to take the monster life by himself because he killed many person that he really loves. The other things which are depicted in those parts are the characteristics of instinct. it includes the pressure, the aim, and the object of instinct. The pressure is described as the motivational things which influence person to do something to get pleasure. It is shown by the monster when he wants to kill all human because his revenge feeling, and the doctor when he wants to fight with the monster because his rage feeling. The second characteristic is the aim of instinct which describe as the actions or wishes that will be done by the person to get pleasure in their life. It is depicted in the characters when the doctor wants to take the monster life with his own hands, and when the monster wants to kill the doctor because he created him with the bad physical condition which make the monster as the unacceptable person in his social life. The last characteristics which is shown by the characters is the object of instinct, it means that the person who do the actions based on their instinct, will get the satisfied feeling from the object of instinct itself. It is shown when the doctor wants to destroy the monster’s head, the monster is being the object of instinct that can give a satisfied for the doctor when Frankenstein really can kill the monster by himself. And it is also shown when the monster killed Elizabeth who is being the doctor’s wife. She is being the object of instinct that will give the satisfied feeling for the monster when he can kill her by his hands. Besides finding how death instinct is done by the characters, this study also find the reasons why aggression is done by them. Based on aggression terms, there are some factors that influence people to do aggression. They includes the biological factor, instinct, anger and frustration feeling. Those factors are shown by the characters, such as Dr. Frankenstein and the monster. It is described when the doctor hunts the monster, he wants kill the monster because he is very angry, it related to the accidents that has been done by the monster to his friends and families in the novel. It is also shown by the monster, when he destroyed many inanimate things such as tress around him, he feels frustration because he cannot injure a human. These feelings become the reason for them to do aggression to another person or thing. REFERENCES Abrams, M.H. 1999. A Glossary of Literary Terms. Seventh Editio. U.S.A : Thomson Learning, inc. Cloninger, Susan. 2004. Theory of Personality : Understanding Person. Fourth Edition. : Pearson Prentice Hall. Feist, Jess and Gregory J. Feist. 2008. Theories of Personality, Seventh Edition. New York: McGraw – Hill Co. Klein, Melanie. 1988. Development In Theory and Practice Volume 1. New York: Taylor & Francis e-Library. Orbach, Israel. 2007. Isr J Psychiatry Relat Sci Vol 44 No. 4. Israel : Bar-Ilan University. Rickman, Richard M. 2008. Theories of Personality Ninth Edition. Belmont: Thomson Higher Education. Rivers, William H.R. 1920. Instinct and The Unconscious A Contribution to A Biological Theory of The Psychoneuroses. Ontario: Christopher D. Green. Schultz, Duane P and Sydney Ellen Schultz. 2009, 2005. Theories of Personality Ninth Edition. Belmont: Wadsworth, Cengage Learning (http://www.phobosdeimos.com/History/Frankenstein/Frankenstein%20History.htm. Retrieved on June, 20th 2013) (http://12013pus.blogspot.com/ 2013/ 06/ sigmund-freud.html. Retrieved on June, 20th 2013) (http://jambeekidul.blogspot.com/2012/05/agresi.html. Retrieved on June, 20th 2013)